Fast and Reliable Locating of Points with the Maximum Value of Total Electromagnetic Field Using a Modern Experimental Method for Radio Coverage in Urban Environment - Petar S. Medjedovic; Darko S. Suka (International Journal of Antennas and Propagation)
This research has been performed within the project “prediction, measurement, and analysis of composite electromagnetic field of artificial radiation sources,” funded by the Ministry of Science and Technology of the Republic of Srpska, Bosnia and Herzegovina. The ultimate goal of the project is the installation of a monitoring network for continuous measurement and recording of nonionizing electromagnetic (EM) radiation levels in the wider area of Banja Luka city centre covering about 10 km2. For this reason it was necessary to make an optimal choice from a dozen of measurement points with the maximum value levels of total EM field. It was a difficult task, because in this case, with the resolution of 5m × 5m, approximately 400,000 points should be examined. Therefore, the pedestrian zones, areas, and routes with significantly smaller surfaces but with the largest flow of people have been examined, so the time required for their mapping with values of total EM field has been reduced to a more realistic framework. In this paper, in the volume allowed by the defined criteria, a fast and reliable experimental method has been described, which has been examined at one of the studied areas in the named project, with surface of 0.008 km2.